2010
DOI: 10.1111/j.1469-8986.2009.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch negativity (MMN), the deviance-elicited auditory deflection, explained

Abstract: The current review constitutes the first comprehensive look at the possibility that the mismatch negativity (MMN, the deflection of the auditory ERP/ERF elicited by stimulus change) might be generated by so-called fresh-afferent neuronal activity. This possibility has been repeatedly ruled out for the past 30 years, with the prevailing theoretical accounts relying on a memory-based explanation instead. We propose that the MMN is, in essence, a latency-and amplitude-modulated expression of the auditory N1 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
475
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(503 citation statements)
references
References 536 publications
(1,030 reference statements)
17
475
3
1
Order By: Relevance
“…The facilitation model shows a strong similarity to a more recent adaptation-based model of the MMN, which proposed that the MMN is generated by fresh-afferent activity of cortical neurons, the latency and amplitude of which is modulated during stimulus repetition (May & Tiitinen, 2010). However, other recent studies using neurobiologically informed computational models (Garagnani & Pulvermü ller, 2011;Wacongne, Changeux, & Dehaene, 2012) found that the MMN is likely to be generated by active cortical predictive mechanisms rather than passive adaptation.…”
supporting
confidence: 60%
“…The facilitation model shows a strong similarity to a more recent adaptation-based model of the MMN, which proposed that the MMN is generated by fresh-afferent activity of cortical neurons, the latency and amplitude of which is modulated during stimulus repetition (May & Tiitinen, 2010). However, other recent studies using neurobiologically informed computational models (Garagnani & Pulvermü ller, 2011;Wacongne, Changeux, & Dehaene, 2012) found that the MMN is likely to be generated by active cortical predictive mechanisms rather than passive adaptation.…”
supporting
confidence: 60%
“…Although the current view of the mechanism-generating MMN is that the divergence of sensory input (deviant stimuli) with the memory trace created by the repetition (standard stimuli) elicits MMN. An alternative explanation claims that the deviant stimulus merely activates new afferent neuronal populations causing the diverging response, and thus the detection of change (Jääskeläinen et al, 2004;May & Tiitinen, 2010;Näätänen, 1992;Paavilainen, Alho, Reinikainen, Sams, & Näätänen, 1991).…”
Section: The Development Of Auditory Erp Componentsmentioning
confidence: 99%
“…This is important, because the differences in stimulus repetitions and the acoustic differences between stimuli alone could cause differences between responses, regardless of whether there actual sensory memory-based change detection processing is involved or not (May & Tiitinen, 2010. Beyond that, Study I is important for the research field in that it contrasts the responses to speech with responses to equally complex non-speech stimuli.…”
Section: Change Detection In Childrenmentioning
confidence: 99%
“…To account for the stronger anterior superior-temporal sources observed for the MMN response compared with N1 responses, previous adaptation models (Jääskeläinen et al, 2004;May & Tiitinen, 2010) assumed different frequency tuning of neuronal responses for anterior and posterior areas of the superior-temporal cortex (non-specific in posterior parts, sharply tuned in anterior parts). However, these assumptions are difficult to maintain in view of current knowledge about adaptation in the auditory system.…”
Section: Experiments 1 -Mmn To Frequency Change In Auditory Areasmentioning
confidence: 99%
“…Several models have been proposed to explain aspects of the brain's ability to automatically detect change (see (Garrido et al, 2009;May & Tiitinen, 2010) for recent reviews). While these different explanations highlight the relevance of different processes, they converge on the importance of short-term mechanisms acting upon, or being driven by, the most recent sensory input.…”
Section: Introductionmentioning
confidence: 99%